Occurrence of Pre- and Postoperative Stress Urinary Incontinence in 105 Patients Who Underwent Tension-Free Vaginal Mesh Surgery for Pelvic Organ Prolapse: A Retrospective Study. (6th February 2014) - Kanasaki, Haruhiko; Oride, Aki; Mitsuo, Tomomi; Miyazaki, Kohji
Abstract : Objective . To examine retrospectively the occurrence of stress urinary incontinence (SUI) in patients who underwent transvaginal mesh repair (TVM) for pelvic organ prolapse (POP). Methods . The presence of preoperative SUI and postoperative changes in SUI was retrospectively analyzed for 105 patients who underwent TVM for POP between September 2009 and September 2012. Results . Preoperative SUI was observed in almost half of the patients (n = 50 ) who underwent TVM surgery. No significant differences were seen in patient age, pelvic organ prolapse quantification (POP-Q) stage, or primary POP complaint between those with and without preoperative SUI. Of the 50 patients with preoperative SUI, SUI was resolved in 14 (28%) following TVM surgery. Of the 55 patients without preoperative SUI, de novo postoperative SUI appeared in 26 (47.3%), of whom approximately half experienced resolution or improvement of SUI within 6 months postoperatively. There was no relationship between preoperative residual urine volume and occurrence of postoperative SUI. Conclusion . TVM surgery is a useful surgical method that can replace traditional methods for treating POP, but sufficient informed consent with regards to the onset of postoperative SUI is required.